Comptes Rendus. Biologies 2020
DOI: 10.5802/crbiol.4
|View full text |Cite
|
Sign up to set email alerts
|

Nerve structures of the heart and their immunohistochemical characterization in 10-week-old porcine foetuses

Abstract: Nerve structures of the heart and their immunohistochemical characterization in 10-week-old porcine foetuses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(79 reference statements)
0
3
1
Order By: Relevance
“…No CGRP‐positive ganglionic cell bodies were identified in our whole‐mount preparations of the piglet atria. This is in sharp contrast to study by Franke‐Radowiecka et al (2020) which reports about CGRP‐positive neuronal somata observed in the hearts of porcine fetuses. Temporary expression of this neuropeptide during prenatal development may explain these differences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…No CGRP‐positive ganglionic cell bodies were identified in our whole‐mount preparations of the piglet atria. This is in sharp contrast to study by Franke‐Radowiecka et al (2020) which reports about CGRP‐positive neuronal somata observed in the hearts of porcine fetuses. Temporary expression of this neuropeptide during prenatal development may explain these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…The revealed abundance of adrenergic NS is in line with the quantity of these cells in the piglet cardiac ventricles (Pauziene et al, 2017). Interestingly, adrenergic NS in the heart of 10‐week‐old porcine fetus composed only about 1.5% of all intrinsic cardiac somata revealed in the study by Franke‐Radowiecka et al (2020), as well as these neural cells were scarce in the heart conductive system of young adult pigs aged 3–6 months (Crick et al, 1999). Thereby, it may be implied that adrenergic as well as cholinergic NS develop throughout the prenatal and the early postnatal periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, there was no presence of nerve fibers containing CART and/or CGRP, although previous studies have described both of these substances in the intracardiac nervous structures [63][64][65][66]. The absence of CGRP positive nerves is especially surprising because this substance in the light of previous studies is known as an important factor participating, among others, in the regulation of the blood flow in vessels located in the heart wall [67], showing protective effects on cardiomyocytes [67,68] and increasing the heart rate [69].…”
Section: Discussionmentioning
confidence: 49%